Mixed polar-nonpolar lipid films as minimalistic models of Tear Film Lipid Layer: A Langmuir trough and fluorescence microscopy study - Olżyńska, Agnieszka; Wizert, Alicja; Štefl, Martin; Iskander, D Robert; Cwiklik, Lukasz (Biochimica et biophysica acta. Biomembranes, 2020)
The Tear Film Lipid Layer (TFLL) covering the surface of the aqueous film at human cornea forms a first barrier between the eye and environment. Its alterations are related to dry eye disease. TFLL is formed by a complex mixture of lipids, with an excess of nonpolar components and a minor fraction of polar molecules. Its thickness is up to 160 nm, hence a multilayer-like structure of TFLL is assumed. However, details of TFLL organization are mostly unavailable in vivo due to the dynamic nature of the human tear film. To overcome this issue, we employ a minimalistic in vitro lipid model of TFLL. We study its biophysical characteristics by using a combination of the Langmuir trough with fluorescence microscopy. The model consists of two-component polar-nonpolar lipid films with a varying component ratio spread on the aqueous subphase at physiologically relevant temperature. We demonstrate that the model lipid mixture undergoes substantial structural reorganization as a function of lateral pressure and polar to nonpolar lipid ratio. In particular, the film is one-molecule-thick and homogenous under low lateral pressure. Upon compression, it transforms into a multilayer structure with inhomogeneities in the form of polar-nonpolar lipid assemblies. Based on this model, we hypothesize that TFLL in vivo has a duplex polar-nonpolar structure and it contains numerous mixed lipid aggregates formed because of film restructuring. These findings, despite the simplified character of the model, seem relevant for TFLL physiology as well as for understanding pathological conditions related to the lipids of the tear film.
Keywords: Fluorescence microscopy; Surface Properties; voda; Langmuir trough; Tears; povrchové vlastnosti; Tear film lipid layer; Lipids; lipidy; lidé; slzy; Microscopy, Fluorescence; Water; rohovka; Cornea; Lipid films; Humans; fluorescenční mikroskopie